Can the mitochondrial malondialdehyde content be an useful tool to distinguish ecological quality of Petromyzon marinus habitat? - Candeias, M (2014)
The sea lamprey is an anadromous species that migrates twice during its life cycle between freshwater and seawater. Microphagous larvae generally spend 4–5 years burrowed in the substrate of rivers and streams before undergoing metamorphosis that ends with the beginning of the juvenile trophic migration. Once metamorphosis is complete, sea lamprey juvenile downstream migrants are fully tolerant to 35 PSU seawater. Pollution resulting from industrial effluents may disturb the seawater acclimatization causing oxidative damages, and ultimately may lead to a decrease of sea lamprey population. The aim of this study was to compare salt acclimation of sea lamprey juveniles captured in river basins with different levels of aquatic pollution, using mitochondrial glutathione and malondialdehyde of gills and liver as markers of physiological stress and cell damages. The results showed that juveniles from Lima basin exhibited the highest levels of mitochondrial malondialdehyde in gills, even though significant changes in the stress markers of mitochondrial gills of all animals subject to salt acclimation were not detected. In addition, an increase in the oxidative damages of hepatic mitochondria of macrophthalmia from Vouga basin suggests the occurrence of metabolic failures with the potential to disturb the capacity to adaptation to the marine environment.